Ethics and Armed Conflict in Afghanistan - Sheerzuy, Wahid (Université d'Ottawa | University of Ottawa, 2020)
Afghanistan’s geopolitical importance to the West and the former USSR has had a tremendous effect on Afghanistan’s people. The country was used as a war zone both in the Cold War and post 9/11 between the United States, Russia, and other countries as well as groups like the Mujahedeen, Al-Qaeda, and Taliban militants. Looking at the country’s historical situation, it is clear that it has been a disaster place for the people of Afghanistan. Thus, they have become more vulnerable to such struggles due to the country’s long war. Conflicts are very common. On many occasions, they are the ultimate constructive drivers of societal change. As Afghanistan has been grappling with different forms of conflicts and civil wars for over four decades which resulted in the death of more than 2 million people and displacements of millions of people, it is important to look at the country’s ongoing conflicts from the ethical point of view (Maley 163). During forty years of conflict starting from 1978, various forms of inhuman and intolerable violence occurred; women have been assaulted, and children have been abused, forced to participate in violence, and are coerced to do labour jobs. Many credible national and international human rights observers have reported the continuous and prolonged killings and tortures of the war prisoners as well as breach of the Geneva accord, and human rights laws. It has also been reported that prisoners have been mass-massacred, and women and children have been group-rapped during the civil war in the 1990s (Maley 198).